4m^3n-4m^2n^2+mn^3-mn因式分解
来源:学生作业帮助网 编辑:六六作业网 时间:2024/12/19 03:30:15
4m^3n-4m^2n^2+mn^3-mn因式分解4m^3n-4m^2n^2+mn^3-mn因式分解4m^3n-4m^2n^2+mn^3-mn因式分解=4m^2n(m-n)+mn(n^2-1)=mn(
4m^3n-4m^2n^2+mn^3-mn因式分解
4m^3n-4m^2n^2+mn^3-mn因式分解
4m^3n-4m^2n^2+mn^3-mn因式分解
=4m^2n(m-n)+mn(n^2-1)
=mn(4m^2-4mn+n^-1)
=mn(2m-n+1)(2m-n-1)
=mn(4m^2-4mn+n^2-1)=mn{(2m-n)^2-1}=mn(2m-n-1)(2m-n+1)
4m^3n-4m^2n^2+mn^3-mn
=4m^2n(m-n)+mn(n^2-1)
=mn(4m^2-4mn+n^-1)
=mn(2m-n+1)(2m-n-1)
希望你能看懂,祝你学习进步
(m-n)(m^5+m^4n+m^3n^2+m²n^3+mn^4+n^5)
已知m-n=4,m、n互为倒数求(-2mn+2m+3n)-(3mn+2n-2m)-(m+4m+mn)的值
因式分解m^3-2m^2n+mn^2-4m^2+4mn+4m
3(m^2n+mn)-4(mn-2m^2n)+mn.要有过程
已知m-n=4,mn=2,求多项式(-2mn+2m+3n)-(3mn+2n-2m)-(m+4n+mn)的值.
已知m-n=3,mn=-3,求(-m-4n-mn)-(2mn-2m-3n)-(3mn+2n-2m)的值
已知m-n=4,mn=-1,求(-2mn+2m+3n)-(3mn+2n-2m)-(m+4n+mn)的值.
若m-n=4,mn=-1,求(-2mn+2m+3n)-(3mn+2n-2m)-(m+4n+mn)
若m-n=4,mn=-1求(9-2mn+2m+3n)-(3mn+2n-2m)-(m+4n+mn)
已知m-n=4,mn=-1,求(-2mn+2m+3n)-(3mn+2n-2m)-(m+4n+mn)的值
已知m-n=3,mn=-1,求多项式-2mn+2m+3n-3mn-2n+2m-4n-m-mn的值
已知m-n=2,mn=1,求多项式(2mn+2m+3n)-(3mn+2n-2m)-(m+4n+mn)的值
已知|m-n-2|与(mn-1)^互为相反数,求(-2mn+2m+3n)-(3mn+2n-2m)-(m+4n+mn)的值
若m-n=4,mn=-1,求(-2mn+m+n)-(3mn+5n-5m)-(m+4n-3mn)的值
因式分解4m^2n(m-n)^2-mn^3(n-m)
m^2+n^2+1=mn+m+n,求3m-4n
(m-2n)^2+(3m-n)(2m+2n)-(2m+n)(2m-n) 已知m+n=4 mn=1
计算:[-m^3n/(m-n)^2]^4*[(n^2-mn)/m]^3/m^4n^10*[(mn-n^2)/m]^6